{Submucosal and Mucosal Infiltration in Tracheobronchial Tree of Diagnosed Small Cell Lung Cancer (Revista de Medicina Clinica, 2023)
Lung cancer is the leading cause of cancer death in the world. Tobacco remains the main factor risk for the development of the disease. Lung cancer is expected to become the sixth leading cause of death by 2030. Most common, compared to its current position (the ninth cause of death). Bronchoscopy is the minimally invasive methodmost important for its diagnosis, this allows us to macroscopically assess the tracheobronchial tree, as well as take samples direct through endobronchial biopsies. We present a case of a 58-year-old man with no previous lung diseases, who We diagnosed through direct exploration with fiberoptic bronchoscopy, where we saw tumor infiltration throughout the tracheobronchial tree.
Keywords: Cancer; lung; infiltration; bronchoscopy